PRAWNOMIĘDZYNARODOWA ISTOTA I PRAWNOKRAJOWE SKUTKI SUKCESJI PAŃSTW. WYBRANE ZAGADNIENIA TEORETYCZNE - Muszyński, Mariusz (Zeszyty Prawnicze, 2016)
INTERNATIONAL LAW AND ITS CONSEQUENCES FOR SUCCESSION OF STATES: SELECTED THEORETICAL ISSUES Summary The succession of states is considered one of the most disputed areas of international law. It depends to a large extent on a state’s policy; the same events may be given completely different evaluations if viewed from different perspectives. Often the norms applied are not detailed enough or they are merely supplementary to settlements made by the states involved. Sometimes the opinion is voiced that succession is nothing more than a kind of practice which is determined only by the fundamental principles of international law, but is not sanctioned by opinio iuris. That is why succession may take so many forms which the theoreticians of international law did not manage arrange in a systematic way until the second half of the 20th century, when they classified its forms according to two general formulas: universal succession and partial succession. Nonetheless the practices different states pursue are still diversified and inconsistent.